2019
DOI: 10.1021/acssensors.8b00942
|View full text |Cite
|
Sign up to set email alerts
|

Generic Neutravidin Biosensor for Simultaneous Multiplex Detection of MicroRNAs via Electrochemically Encoded Responsive Nanolabels

Abstract: Current electrochemical biosensors for multiple miRNAs require tedious immobilization of various nucleic acid probes. Here, we demonstrate an innovative approach using a generic neutravidin biosensor combined with electrochemically encoded responsive nanolabels for facile and simultaneous multiplexed detection of miRNA-21 and miRNA-141. The selectivity of the biosensor arises from the intrinsic properties of the electrochemically encoded responsive nanolabels, comprising biotinylated molecular beacons (biotin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…These strategies have been shown to push the detection limit to nanomolar or even attomolar levels [30], which may further enhance the diagnostic power of miRNA-based liquid biopsy. Furthermore, multiplexed detection of miRNAs can be achieved by using CRISPR/Cas9 [31,32] or CRISPR/Cas12a [33] techniques, surface-enhanced Raman scattering (SERS) biosensors [34], and the biotin-neutravidin reaction [35]. Multiplexed miRNA detection may help further distinguish the origin of cancer and elevate detection specificity.…”
Section: Discussionmentioning
confidence: 99%
“…These strategies have been shown to push the detection limit to nanomolar or even attomolar levels [30], which may further enhance the diagnostic power of miRNA-based liquid biopsy. Furthermore, multiplexed detection of miRNAs can be achieved by using CRISPR/Cas9 [31,32] or CRISPR/Cas12a [33] techniques, surface-enhanced Raman scattering (SERS) biosensors [34], and the biotin-neutravidin reaction [35]. Multiplexed miRNA detection may help further distinguish the origin of cancer and elevate detection specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the assaying of multiple miRNA markers from one sample is necessary for accurate detection and higher specificity. 45 Only handful of research has been reported thus far on the multiplexed and simultaneous detection of only two or three miRNAs using biosensors for early BC detection [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] from the body fluids. To the best of our knowledge, there is no systematic review conducted on the electrochemical biosensors for multiplexed DCIS miRNAs detection.…”
Section: Dcis Stages Grades and Incidencementioning
confidence: 99%
“…Comparative electrochemical performances for miRNA-141 and miRNA-21 electrochemical detection.-Two of the miRNAs namely miRNA-21 and miRNA-141 which are reported to be upregulated in the human plasma due to DCIS has been evaluated by few authors. 45,47,51,54,57,58,60 The highest performance in terms of limit of detection (LoD) has been reported by Mohammadniaei et al using an unique amplification strategy introduced by combining MXene (Ti 3 C 2 T x ) and a duplex-specific nuclease (DSN) resulting in attomolar and quantification for duplex miRNAs on a single platform and demonstrated its detection from total plasma. The MXene with higher surface area is loaded with gold nanoparticles (AuNPs) and drop casted on a dual screen-printed gold electrode and coimmobilized with DNA target probes.…”
Section: Ecs Sensors Plus 2022 1 021602mentioning
confidence: 99%
“…Apart from the reporter molecule, nanomaterials were also employed to generate differential signal that is suitable for multiplex detection of miRNA. Electrochemically encoded responsive nanolabels comprising biotinylated molecular beacons and AuNPs or AgNPs were applied to generic neutravidin biosensor for the simultaneous multiplexed detection of miR-21 and miR-141 [92]. Stripping square-wave voltammetry (SSWV) was performed to analyze the electrochemical signal generated from the gold and silver label, resulting in limit of detection of 0.3 and 10 pM for miR-21 and miR-141, respectively.…”
Section: Simultaneous Detection Of Mirnasmentioning
confidence: 99%